Improving the Students’ Narrative Monologue Skills at the Grade XI-IPS 2 of the Public Senior High School 7 Malang by Using the Picture Series Media - misianto misianto (Universitas Merdeka Malang, 2018)
The English Curriculum 2013 of Senior High School requires the students to be skilful in the narrative monologue. The existing model of teaching narrative monologue so-called text memorization applied by the English teachers proves boring to the students. Such model assigns the students to memorize the text provided by the teacher and retell it. This Classroom Action Research (CAR) aimed at describing the model of teaching narrative monologue by using picture series media for both overcoming the problems faced by the students when they presented narrative monologue and improving the students’ skills of narrative monologue. Based on the collected data, the use of picture series media for teaching narrative monologue proved effective in both improving the students’ skills of narrative monologue and motivating the students to present a narrative monologue. Results of Cycle 1 were as follows: (1) from the aspect of developing ideas (coherence), it showed that there were 1 student who got the score of 2 (10.71%), 11 students with the score of 3 (89.29%), and 16 students with the score of 4 (57.1%); and (2) from the aspect of conveying the message (fluency), it showed that there were 2 students who got the score of 2 (7%), 16 students with the score of 3 (57%), and 10 students with the score of 4 (36%). The average value of the class in narrative monologues using picture series media in cycle 1 was 82.6. Results of Cycle 2 were as follows: (1) from the aspect of developing ideas (coherence), it showed that there were 1 student who got the score of 1 (4%), 20 students with the score of 3 (80%), and 4 students with the score of 4 (16%); and (2) from the aspect of conveying the message (fluency), it showed that there were 1 student who got the score of 1 (4%), and 24 students with the score of 4 (96%). The average value of the class in a narrative monologue using picture series media in cycle 2 was 85.4.